Connectivity but not recruitment: Response of the fish community to a large‐scale flood on a heavily regulated floodplain. Issue 3 (31st January 2020) - Cruz, Derrick O.; Kingsford, Richard T.; Suthers, Iain M.; Rayner, Thomas S.; Smith, James A.; Arthington, Angela H.
Abstract: Recent environmental flow management in the Murray–Darling basin, south‐eastern Australia, has centred on restoring natural flooding regimes to meet ecological requirements, including the promotion of native fish recruitment, despite uncertainty about the effectiveness of managed environmental flooding. This study investigated recruitment responses of small‐bodied native and non‐native fish species to a large natural flood, supported by managed environmental flows in the Macquarie Marshes of the Murray–Darling basin. We surveyed the fish community within the heavily regulated, dryland floodplain system of the marshes, the year after breaking of the Millennium drought (2002–2009). During the spring–summer of 2010, the Macquarie Marshes experienced a one‐in‐10‐year flood, sustained by two environmental flow allocations, flooding 174, 000 ha of floodplain. Five native species were collected across the nine study sites. Two non‐native species were particularly abundant during the flood, outnumbering the five native species in a ratio of 32:1, with Gambusia holbrooki the most abundant species, comprising 87% of all native and non‐native individuals captured. There was no marked effect of flood stage on the total abundance of small‐bodied native or non‐native fishes, but the composition of the fish community varied between surveys of the rising and falling phases of the flood. We did not capture any larval or post‐larval fish despite using a variety of suitable sampling methods. The lack of larvae in the Macquarie Marshes, following extensive flooding, most likely reflected the overall poor condition of native fish communities and low standing stocks of mature fish, resulting from deleterious long‐term effects of flow regulation exacerbated by drought. A gradual rebuilding of ecosystem health, fish health, and resilient fish populations by active management of environmental flows to impose more natural boom and bust dynamics may be needed to restore fish reproduction and recruitment in this regulated river.